Kolaborasi Universitas_industri: Tinjauan Konseptual Mekanisme Transfer Pengetahuan dari Universitas ke Industri - Lina Anatan (Jurnal Manajemen Maranatha, 2008)
University-industry collaboration (UIC) has become an essential element of the research endeavours both in academic institutions and industrial sectors. UIC contribute significant resources not only financial resources but also intellectual resources to scientist and firms related. By managing UIC, we expected to invest the development of university research and business research capabilities on current research strength, and to link the research strength to the solution of industry problem which lead to the improvement of business performance and finally will effect the improvement of economic growth. These relationships also play an important role in bringing beneficial and innovative product to the public. This paper discussed what UIC is, the important of UIC in knowledge economy era, UIC characteristics from university and industry perspective, the mechanism of knowledge transfer through UIC and some example of the implementation of UIC in Indonesia.